Spectrum of Posttransplant Lymphoproliferations in NSG Mice and Their Association With EBV Infection After Engraftment of Pediatric Solid Tumors. Issue 3 (May 2020) - Tillman, Heather; Vogel, Peter; Rogers, Tiffani; Akers, Walter; Rehg, Jerold E.
Pediatric patients receiving solid organ transplants may develop lymphoproliferative diseases, including graft-versus-host disease (GvHD) and posttransplant lymphoproliferative diseases (PTLDs). We characterized lesions in 11 clinically ill NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice that received pediatric-patient-derived solid tumors (PDXs) and developed immunodeficiency-associated lymphoproliferations comparable to GvHD and PTLDs over a period of 46 to 283 days after implantation. Lymphoproliferations were diffusely positive for human-specific biomarkers, including NUMA1, CD45, and CD43, but lacked immunoreactivity for murine CD45. Human immune cells were CD3-positive, with subsets having immunoreactivity for CD4 and CD8 as well as PAX5, CD79a, and IRF4, resulting from populations of human T and B cells present within the xenotransplants. Tissues and organs infiltrated included mucocutaneous zones (oral cavity and perigenital and perianal regions), haired skin, tongue, esophagus, forestomach, thyroid, salivary glands, lungs, liver, kidneys, spleen, lymph nodes, bone marrow, and brain. In 4 of 5 mice with PTLD, Epstein-Barr virus (EBV)-encoded small RNAs (EBERs) were detected by in situ hybridization in PAX5 + human B cells associated with the PDX ( n = 1/4) or with engrafted human immune cells at other anatomic locations ( n = 4/11). One of the 4 mice had an EBV-associated human large B-cell lymphoma. NSG mice receiving xenotransplants can develop combinations of GvHD, EBV-driven PTLD, and B-cell lymphoma similar to those occurring in human pediatric patients. Therefore, pediatric xenotransplants should undergo histopathologic and immunohistochemical assessment upon collection to ensure that the specimen is not a lymphoma and does not contain lymphoma cells because these neoplasms can morphologically mimic small round blue cell pediatric solid tumors.